Designing Compression Sportswear in Cad Systems (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The article provides information about computer-aided design systems, their capabilities, design features of compression sportswear, anthropometric indicators of athletes, 3D design capabilities and assessment of clothing fit on a virtual mannequin. Also, this study explores the application of computer-aided design (CAD) systems in creating compression sportswear, emphasizing their role in automating design processes and enhancing garment precision. It examines key anthropometric considerations, the integration of 3D modeling, and virtual fit assessments on mannequins. The findings suggest that while CAD systems improve efficiency and accuracy, further refinement in virtual modeling capabilities is essential to optimize material properties and enhance consumer experience. The study highlights future directions for CAD development in textile engineering.